The Effect of Return Expectations and Perceived Risk on Intention to Invest in Crypto Assets: Evidence from Indonesian Investors - Vera Kristanti Dewi, Made; Gede Sri Diwya, Ketut (Jurnal Ilmiah Manajemen & Bisnis, 2024)
Investment in cryptocurrency offers high potential returns but is also accompanied by significant risks due to substantial price fluctuations. The volatile nature of crypto assets makes them a subject of intense interest and caution among investors. Before engaging in transactions, investors typically evaluate the potential risks and returns they may obtain, balancing the allure of high profits against the possibility of significant losses. Therefore, investors' intention to invest in crypto assets is based on these two factors: return expectations and risk perception. This study employs multiple linear regression analysis using SPSS software to examine the relationship between these variables. The sampling technique used is purposive sampling, with a sample size determined to be between 45 and 90 respondents to ensure statistical validity. The questionnaire was distributed online to the crypto asset investor community in Indonesia, and respondents provided answers using a Likert scale from 1 (Strongly Disagree) to 5 (Strongly Agree). The data analysis reveals that return expectations have a positive and significant effect on investment interest in crypto assets. Additionally, risk perception also has a positive and significant effect on investment interest in crypto assets, indicating that even perceived risks do not deter investment interest, possibly due to the high return potential. Furthermore, return expectations and risk perception simultaneously have a positive and significant effect on investment interest in crypto assets, suggesting that both factors jointly influence investment intentions. These findings provide valuable insights for investors and market participants in understanding the factors influencing investment decisions in cryptocurrency, highlighting the importance of managing both expected returns and perceived risks in investment strategies.